Artificial intelligence applications in entrepreneurship and online education: insights from bibliometric and topic modeling analyses - Alpürk, Kemal; Ayaz, Ahmet; Altınay, Fahriye; Altınay, Zehra; Berigel, Duygu Solak; Dağlı, Gökmen (Frontiers in Education, 2025)
IntroductionThe convergence of AI, entrepreneurship, and online education has accelerated, yet their intersection remains under-mapped.MethodsWe analyzed 489 peer-reviewed articles (2010–2024) from Scopus and Web of Science using Bibliometrix for bibliometrics and LDA topic modeling (Gensim/pyLDAvis).ResultsFive thematic clusters emerged; “Teaching and Pedagogical Innovations” and “Innovative Learning Models & Entrepreneurship” were most prominent. China, the UK, and the US were leading contributors. Topic trajectories show rising emphasis on AI-enabled pedagogy and digital integration.DiscussionThe dual bibliometric–semantic approach reveals underexplored themes and actionable directions for digital entrepreneurship and AI-enhanced education, informing policy and institutional strategy.